A Comparative Study of Serum Amyloid A2 with Anti-cyclic Citrullinated Peptide antibody in the prognosis of a Group of Rheumatoid Arthritis Patients in Iraq - Oglah, Ali A.; Abid Mohammed , Khalil I.; Alosami, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Rheumatoid arthritis (RA) is an inflammatory disease of unknown etiology characterized by joint inflammation and the presence of autoantibodies, mostly Anti-cyclic citrullinated peptide antibody (ACCP) which are released when the body loses its ability to distinguish between self and foreign molecules. Serum amyloid A2 (SAA2) is an acute phase protein produced in response to inflammatory conditions including RA.Objectives: To investigate the prognostic ability of SAA2 in comparison with ACCP and the prediction of disease activity and response to treatment by Methotrexate and Etanercept in Iraqi RA patients.  Patients and methods: A case control study, on a total of 150 individuals; 100 patients and 50 healthy controls. The study was carried out between November 2021 to February 2022 in Baghdad Teaching Hospital. The patients were recruited according to the American College of Rheumatology 2010 criteria. The biomarkers’ levels were measured by enzyme-linked immunosorbent assay.Results: The levels of ACCP and SAA2 in RA patients were significantly higher compared to healthy controls (p